The effects of storage conditions and ascorbic acid treatment on shelf life of cauliflower, broccoli, and rutabaga - Didar Farid Kareem Al-Shateri 1992- (2022)
This study was a part of the project “Improved quality, shelf life and reduced waste in the value chain of Icelandic vegetables” (Bætt gæði, geymsluþol og minni sóun í virðiskeðju íslensks grænmetis, Matis Project no. 62666). In Iceland, vegetables are difficult to cultivate outdoors due to the cool climate. Yet, cauliflower, broccoli and rutabaga yield may exceed market demand. Several studies abroad confirm that the sensory quality of vegetables has a significant impact on consumer acceptability and purchase behaviour. Therefore, it is necessary to find ways to prolong the shelf life of these vegetables and preserve their quality and reduce waste. This study aimed to obtain new knowledge about the sensory properties (appearance, odour, flavour, texture, and overall quality) and quality of cauliflower, broccoli, and rutabaga under two different conditions (i.e., packed with Clarus polyolefin shrink film and unpacked) during storage at regulated storage conditions of 0°C-2°C temperature and 90%-95% humidity, Additionally the aim was to design sensory schemes to measure the sensory quality of vegetables. Lastly, the aim was to investigate the effect of ascorbic acid (i.e., vitamin C) as a preservative to extend the shelf life of fresh-cut cauliflower and broccoli at regulated storage of 0°C-2°C temperature and 90%-95% humidity. The study was divided into experiment 1 (packed and unpacked vegetables) and experiment 2 (effect of ascorbic acid). The experiments were conducted in September to December 2021. A sensory scheme was designed for each vegetable (i.e., cauliflower, broccoli, and rutabaga). Samples for both experiments were obtained from local farms. Parameters measured in both experiments were sensory evaluation by eight trained sensory panellists, microbial count, water content, vitamin C content, weight loss, and colour change using CIL lab L, and b. Temperature and humidity were monitored and recorded throughout the studies. In experiment 1, sensory properties of all three vegetables (cauliflower, ...